Mapping for environmental planning the basin of Córrego Rico, São Paulo - Rodrigues, Flávia Mazzer [UNESP]; Pissarra, Teresa Cristina Tarlé [UNESP]; Campos, Sergio [UNESP]; Migliaccio, Kati White; Rodrigues, Carlos Tiago Amâncio (My University, 2013)
The landuse is usually an human phenomenon that occurs over the years, due to population increase. The territorial knowledge is needed, and is the first step for environmental planning to implement conservation practices on agricultural production system. This study aimed to develop thematic maps as: hydrography, soil, slope, land use, and subbasins to obtain the main geomorphic morphometric data (physical) of the Córrego Rico Watershed. The techniques of remote sensing and geographic information system were used to elaborate the maps and for calculating the geomorphological data, as area, altitude and length of the drainage net, which were submitted to multivariate statistics. The Córrego Rico Watershed has an area of 563 km2 . The predominant slopes were 3-8%, with 55.3% of the total area; and the main use was sugar cane. The soils that predominate in the area are Oxisols towards the Mogi-Guaçú river mouth and Ultisols at the upstream of the basin.
Keywords: Soil; Slope; Land use